Mobing v babištvu - Majhenič, Janja (Obzornik zdravstvene nege, 2012)
Introduction: Mobbing or violence at workplace is a prevailing social phenomenon which can be manifested in various forms. It is present in all sectors, especially in health care, due to its strict hierarchical regulation.Destructive workplace conflicts among health professionals can affect also the clients and the quality of care provided. Early detection, solution of conflicts and prevention of mobbing is therefore of crucial importance. The aim of the article is to present a general review of available literature on mobbing in the workplace with special emphasis on mobbing in midwifery. Methods:The descriptive method of literature review was used. The data were collected from EBSCOhost, CINAHL and Medline databases. Discussion and conclusion: Foreign studies confirm that mobbing is present also in midwifery. Oftentimes, the targets of vertical and horizontal psychological harassment experience significant and long-lasting psychosomatic health problems and social consequences. Mobbing has been observed also among midwifery students. Indicative are the research results from Great Britain, according to which, half of the midwives reported some form of mobbing. Unhealthy and tenuous personal relationships often drive midwives to leave their profession. The high prevalence rate of workplace mobbing established in the study highlights the need for prevention, efficient interventions and a compliance with ethical code of this humane profession.
Keywords: babištvo; midwifery; mobbing; mobing; nasilje na delovnem mestu; psihično nasilje; psychological harassment; workplace violence